Evaluation of Olgun Çocuk Dergisi [Mature Child Magazine] (1935) within the Scope of Raising National and Historical Consciousness of Children - Tolgahan Ayantaş; Cengiz Dönmez (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study sought to evaluate Olgun Children’s Journal (1935) within the scope of the efforts of adding nation and history awareness to children by using document examination which is among qualitative research methods. Olgun Children’s Journal which was issued for the first time on 16 February 1935 was a children’s journal which ended its publication life with its 13th and final issue on 25 May 1935. Specific sections of the journal in every issue were Let’s Learn the Statesmen of the Nation, One Mustafa for a Thousand Enemies, Cinema with Art, In the Animal Land, The Scholar Investigating, Adventures of Yumurcak, Our Articles and Riddles-Puzzles. At the end of the study, we observed that the journal personally reflected the understanding and conditions of the era (1930s) and was on the prowl of imbuing children with the opinions of national unity and solidarity in line with the perspective and understanding of the era. The study found that the journal included sub texts related to the Surname Act (1934) in society and efforts of simplification of language, mentioned the Dardanelles War and the War of Independence, stressed the virtues of the Turkish Nation and significance of Atatürk as a leader and tried to raise nation and history awareness in children by this way. The journal accepted children as adults, stressed that children had an ability of achieving even the most difficult tasks and tried to raise consciousness reflecting the historical context in the Turkish children. In addition, the journal designed specific sections for children to have fun and enjoy themselves.